Sikap Pengguna terhadap Pedestrian Friendly Jalur Pedestrian Jalan Gajah Mada di Kota Pontianak - Achmad Eko Yanuar; Aryasa Bijak Utama (Vokasi: Jurnal Publikasi Ilmiah, 2022)
The trade and service area in a city is the lifeblood of a city's growth and also as a tourist attraction in a city if it is well organized in terms of facilities and infrastructure because it provides convenience in transactions as well as a means of recreation. One of the main means of the trade area is the pedestrian path in the area. Likewise with the pedestrian path in the corridor area of ​​Jalan Gadjah Mada which is the main trading area of ​​Pontianak city where the condition of the pedestrian path does not seem to provide maximum hospitality and comfort or pedestrian friendly for the community. This is evidenced by the lack of people to use the pedestrian path. This research approach uses descriptive research methods that aim to provide a systematic, factual, quantitative and qualitative description of the facts and characteristics of a particular population or area. Based on the above, the results to be achieved from this research are to be able to describe how the attitude of the community, especially users of the pedestrian path on Jalan Gadjah Mada towards the pedestrian friendly path, which will be written in the form of a scientific journal and complete the teaching materials for the City Design Concept Theory course. At the same time, it is hoped that it can provide input for local governments and consultants in planning and designing pedestrian pathways for road corridors in the future.